COMPARACIÓN DEL EFECTO DE DOS DILUYENTES SOBRE LA FERTILIDAD POTENCIAL DE SEMEN CANINO REFRIGERADO - Sánchez R., Alfonso (2006)
Twenty canine ejaculates (2nd fraction) were obtained by digital manipulation with the purpose of evaluating the effect of two extenders on the preservation of canine spermatozoa stored at 4 °C. Each ejaculate was evaluated through a spermiogram and the hypo-osmotic swelling test (HOST). The ejaculates were fractioned and diluted in a rate of 1:3 using egg yolk + TRIS + glucose + antibiotic (EYT) (365 mOsm/kg, pH 6.8) and skimmed milk (0.5% fat, UHT-treated) + antibiotic (SM) (272 mOsm/kg, pH 6.8). Progressive motility (PM) was 95.7 ± 3.6% and the HOST response was 79.8 ± 6.6% in fresh semen. In order to compare the effect of the two extenders on the preservation of the potential fertility, the PM and HOST were evaluated after 24, 48, 72, and 96 hours of storage at 4 ºC. The values of PM and HOST for EYT were significantly higher compared to SM at all times (p<0.05). Nevertheless, the PM (>70%) and HOST (>60%) observed in all evaluation periods, independently of the type of extenders, surpassed the minimum values established as appropriate for the use of refrigerated canine semen for artificial insemination. In conclusion, the skimmed milk extender proved to be an efficient, practical, and economical method for preserving semen over a period of 3 to 4 days.